PERLINDUNGAN HUKUM UMKM INTERNASIONAL UNTUK KESEJAHTERAAN MASYARAKAT BERDASARKAN KEADILAN SOSIAL - Pratama, Rinanda Bagus Anarta (Legal Standing : Jurnal Ilmu Hukum, 2024)
One of the efforts that can realize the welfare of the people is to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) to be able to develop in global competition. This research aims to find out the potential and problems of MSME development and to find out the legal protection for MSMEs implementing international trade in the context of improving people's welfare based on social justice. This type of research is normative juridical with a statutory approach, conceptual approach, and historical approach. The results of this study indicate that the potential in the development of MSMEs implementing international trade is that MSMEs are the most dominant form of business in Indonesia, MSMEs are able to absorb labor significantly, MSMEs are able to improve community welfare. Furthermore, the obstacles in the development of MSMEs implementing international trade are divided into 2, namely external obstacles including access to banking funding is still difficult for most MSMEs today, so many MSMEs still use personal funds rather than bank loans, inefficient bureaucratic services, and high infrastructure costs. As for the internal barriers, they are institutional and human resources, production and marketing, intellectual capital. The basis of legal protection for MSMEs implementing international trade in the context of improving people's welfare based on social justice is the principles of international trade, references to sources of international trade law, UU No. 20 of 2008 concerning MSMEs, Government Regulation No. 17 of 2013 concerning the Implementation of UU No. 20 of 2008, UU No. 7 of 2014 concerning Trade, Government Regulation No. 7 concerning the Ease, Protection, and Empowerment of Cooperatives and MSMEs, and UU No. 11 of 2020 concerning Job Creation.